Design and development of groove micromixer for laminar blood-reagent mixing - Abdul Rahim, Suraya (2013)
Mixing of two fluids is an essential process for most of microfluidic device for Biomedical Micro-Electro-Mechanical System (Bio-MEMS) application. Mixing also important in Lab-On-Chip (LOC) system because the chemical reaction carried out in this system requires on-chip mixing. Mixing performance in this system relies mainly on effective and rapid mixing of sample and reagent. Therefore, development of groove micromixer for application of blood and reagent mixing carried out in this project. In this study, two fluids involve in the mixing, which is the blood and reagent (two type of reagent with lower and higher viscosity compared to blood). Two pattern of the groove namely oblique groove and herringbone groove were designed and simulated using CoventorWare2010 software at low Reynolds number. The design of groove micromixer obtained by analyzing the geometries effect of groove pattern on mixing performance of blood and reagent with the visualization of simulation and evaluation of mixing performance for difference geometry parameter of groove micromixer. In this study, it has been demonstrated that the Y-Shape mixer with the groove structure located at the floor of the mixing channel increased the mixing performance. Thus, the simulation result in this study shows that mixing performance can be enhanced when depth and width of groove is 40% of the channel width with the angle of an oblique groove is 45º. Whereas for the herringbone mixer, enhancement of mixing performance occured when the depth and width of herringbone groove is 25% of the channel width with the approximation of asymmetric index is quarter of the width of mixing channel.